REVIEW - Sânziana Ionescu; Laurenţiu Simion; Elena Chitoran; V. Rotaru; Ciprian Cirimbei; Octavia Luciana Madge; Adina Ene; Mădălina Radu; Ariana Neicu; Marian Marincaş (Oncolog-Hematolog.ro)
Neuroendocrine tumors of the small bowel: a literature review